HIV provider and patient perspectives on the Development of a Health Department "Data to Care" Program: a qualitative study - Julia C. Dombrowski; James W. Carey; Nicole Pitts; Jason Craw; Arin Freeman; Matthew R. Golden; Jeanne Bertolli (BMC, 2016)
Abstract Background U.S. health departments have not historically used HIV surveillance data for disease control interventions with individuals, but advances in HIV treatment and surveillance are changing public health practice. Many U.S. health departments are in the early stages of implementing "Data to Care" programs to assists persons living with HIV (PLWH) with engaging in care, based on information collected for HIV surveillance. Stakeholder engagement is a critical first step for development of these programs. In Seattle-King County, Washington, the health department conducted interviews with HIV medical care providers and PLWH to inform its Data to Care program. This paper describes the key themes of these interviews and traces the evolution of the resulting program. Methods Disease intervention specialists conducted individual, semi-structured qualitative interviews with 20 PLWH randomly selected from HIV surveillance who had HIV RNA levels >10,000 copies/mL in 2009-2010. A physician investigator conducted key informant interviews with 15 HIV medical care providers. Investigators analyzed de-identified interview transcripts, developed a codebook of themes, independently coded the interviews, and identified codes used most frequently as well as illustrative quotes for these key themes. We also trace the evolution of the program from 2010 to 2015. Results PLWH generally accepted the idea of the health department helping PLWH engage in care, and described how hearing about the treatment experiences of HIV seropositive peers would assist them with engagement in care. Although many physicians were supportive of the Data to Care concept, others expressed concern about potential health department intrusion on patient privacy and the patient-physician relationship. Providers emphasized the need for the health department to coordinate with existing efforts to improve patient engagement. As a result of the interviews, the Data to Care program in Seattle-King County was designed to incorporate an HIV-positive peer component and to ensure coordination with HIV care providers in the process of relinking patients to care. Conclusions Health departments can build support for Data to Care efforts by gathering input of key stakeholders, such as HIV medical and social service providers, and coordinating with clinic-based efforts to re-engage patients in care.